Adenylyl Cyclase Subtype 1 is Essential for Late-Phase Long Term Potentiation and Spatial Propagation of Synaptic Responses in the Anterior Cingulate Cortex of Adult Mice. (10th October 2014) - Chen, Tao; O'Den, Gerile; Song, Qian; Koga, Kohei; Zhang, Ming-Ming; Zhuo, Min
Long-term potentiation (LTP) is a key cellular mechanism for pathological pain in the central nervous system. LTP contains at least two different phases: early-phase LTP (E-LTP) and late-phase LTP (L-LTP). Among several major cortical areas, the anterior cingulate cortex (ACC) is a critical brain region for pain perception and its related emotional changes. Periphery tissue or nerve injuries cause LTP of excitatory synaptic transmission in the ACC. Our previous studies have demonstrated that genetic deletion of calcium-stimulated adenylyl cyclase 1 (AC1) or pharmacological application of a selective AC1 inhibitor NB001 blocked E-LTP in the ACC. However, the effect of AC1 on L-LTP, which requires new protein synthesis and is important for the process of chronic pain, has not been investigated. Here we tested the effects of NB001 on the ACC L-LTP and found that bath application of NB001 (0.1 μM) totally blocked the induction of L-LTP and recruitment of cortical circuitry without affecting basal excitatory transmission. In contrast, gabapentin, a widely used analgesic drug for neuropathic pain, did not block the induction of L-LTP and circuitry recruitment even at a high concentration (100 μM). Gabapentin non-selectively decreased basal synaptic transmission. Our results provide strong evidence that the selective AC1 inhibitor NB001 can be used to inhibit pain-related cortical L-LTP without affecting basal synaptic transmission. It also provides basic mechanisms for possible side effects of gabapentin in the central nervous system and its ineffectiveness in some patients with neuropathic pain.